2005
DOI: 10.1063/1.1935135
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure formation during deposition of TiN∕SiNx nanomultilayer films by reactive dual magnetron sputtering

Abstract: Growth of multilayer or superlattice thin films has shown various degrees of hardness enhancements often exceeding the individual hardness of the materials involved. Typically the hardness increases with decreasing wavelength until a maximum value is reached in the nm range, after which the hardness decreases with further decrease in wavelength 1,2 . Different theories have been developed in order to explain the observed increase in hardness. Koehler 3 showed theoretically a hardness increase for materials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 42 publications
6
59
1
1
Order By: Relevance
“…9 where the hardness versus the layer period shows a negative linear relationship, similar to what has been reported for other multilayered thin films. 32 The monolithic Ti 0.34 Al 0.66 N shows a drastic decrease in hardness at 950°C which is related to the decomposition of metastable c-AlN into stable h-AlN. The transformation is accompanied by a ϳ20% unit cell volume increase and a loss of the coherency and thus increase the possibility of dislocations movments.…”
Section: B Influence Of Multilayer Period and Heat Treatments On Thementioning
confidence: 99%
“…9 where the hardness versus the layer period shows a negative linear relationship, similar to what has been reported for other multilayered thin films. 32 The monolithic Ti 0.34 Al 0.66 N shows a drastic decrease in hardness at 950°C which is related to the decomposition of metastable c-AlN into stable h-AlN. The transformation is accompanied by a ϳ20% unit cell volume increase and a loss of the coherency and thus increase the possibility of dislocations movments.…”
Section: B Influence Of Multilayer Period and Heat Treatments On Thementioning
confidence: 99%
“…8 Also two-phase nanocrystalline materials in the form of multilayers exhibit an increased hardness compared to their constituents due to the difference in elastic properties between the layers that hinder dislocation motion, 9 most clearly seen in nanoscale multilayers. 10,11 The decomposition of metastable single-phase films can also act to improve the hardness at elevated temperature as a two-phase structure is formed. The most studied of these is the TiAlN system where age hardening upon annealing of thin films was first observed.…”
Section: Introductionmentioning
confidence: 99%
“…Their investigation results indicated that the super-hardness of Ti-Si-N coatings is related to the preferential formation of TiN (111) polar interfaces with a thin β-Si 3 N 4 -derived layer [4][5][6]. In 2005, 2006 and 2007 Söderberg et al reported a transmission electron microscopy examination that showed a transition from epitaxially-stabilized growth of crystalline SiN x to amorphous growth as the layer thickness increased from 0.3 nm to 0.8 nm [7][8][9]. In 2007, and in accordance with the HRTEM and ab initio studies, Kong et al and Hultman et al respectively denoted that the interface in superhard TiN-SiN nanocomposites is crystalline [10,11].…”
Section: Introductionmentioning
confidence: 98%